2013
DOI: 10.5867/medwave.2013.03.5643
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in the hospital, a narrative review

Abstract: Delirium is a common complication in hospitalized patients, particularly the elderly and those with cognitive impairment. It has been associated with higher mortality, prolonged hospitalization, cognitive impairment, higher rates of institutionalization at discharge and higher costs for healthcare systems. Its pathophysiology is poorly understood, and more recently a predominantly inflammatory origin has been proposed, which could explain its pervasiveness and association with underlying conditions. Clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In oncology patients, delirium severity was negatively associated with patient delirium recall and was non-significantly associated with delirium-related patient distress P = 0.09) [19][20][21]. A study reported 105 ICU patients, there was a significant positive correlation between less severe delirium (measured by Neelson and Champagne, NEECHAM, confusion scale) and higher Short Form-20 (SF-20) scores using univariable analyses in physical function (r = 0.35), role function (r = 0.31) and health perception (r = 0.25) at 3 months, and with physical function (r = 0.27), role function (r = 0.34), social function (r = 0.30) and mental health (r = 0.28) at 6 months [22,23].…”
Section: Discussionmentioning
confidence: 93%
“…In oncology patients, delirium severity was negatively associated with patient delirium recall and was non-significantly associated with delirium-related patient distress P = 0.09) [19][20][21]. A study reported 105 ICU patients, there was a significant positive correlation between less severe delirium (measured by Neelson and Champagne, NEECHAM, confusion scale) and higher Short Form-20 (SF-20) scores using univariable analyses in physical function (r = 0.35), role function (r = 0.31) and health perception (r = 0.25) at 3 months, and with physical function (r = 0.27), role function (r = 0.34), social function (r = 0.30) and mental health (r = 0.28) at 6 months [22,23].…”
Section: Discussionmentioning
confidence: 93%